2009
DOI: 10.2117/psysoc.2009.163
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Rape Myth Acceptance and Belief in a Just World on Victim Blame Attribution: A Study in Japan

Abstract: This study examined the moderating role of rape myth acceptance (RMA) and belief in a just world (BJW) on victim blame attribution in either an alleged stranger or date rape case. As hypothesized, RMA and BJW were both significant predictors of victim blame behavior for the Japanese college students who participated in the study. Further, Japanese participants blamed the victim of date rape more than the victim of the stranger rape. The similarities and differences between findings from this study and those fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
1
12
0
4
Order By: Relevance
“…It has been hypothesized that observers holding stronger rape myth beliefs will blame victims more than people without such strong beliefs and research has consistently provided evidence for this correlation. Rape myth acceptance is found to be a significant predictor of rape victim blaming (Mason, Riger, & Foley, 2004;Yamawaki, 2009), and rape perpetrator blaming (Kopper, 1996;Sleath & Bull, 2010), with observers scoring high on rape myth acceptance tending to blame the victim more and the perpetrator less. Furthermore, observers with high levels of rape myth endorsement generally minimize the rape to a greater extent (Newcombe et al, 2008), and are less likely to believe that a rape has actually occurred (Mason et al, 2004), than people who endorse rape myths to a lesser extent.…”
Section: Rape Myth Acceptancementioning
confidence: 93%
See 3 more Smart Citations
“…It has been hypothesized that observers holding stronger rape myth beliefs will blame victims more than people without such strong beliefs and research has consistently provided evidence for this correlation. Rape myth acceptance is found to be a significant predictor of rape victim blaming (Mason, Riger, & Foley, 2004;Yamawaki, 2009), and rape perpetrator blaming (Kopper, 1996;Sleath & Bull, 2010), with observers scoring high on rape myth acceptance tending to blame the victim more and the perpetrator less. Furthermore, observers with high levels of rape myth endorsement generally minimize the rape to a greater extent (Newcombe et al, 2008), and are less likely to believe that a rape has actually occurred (Mason et al, 2004), than people who endorse rape myths to a lesser extent.…”
Section: Rape Myth Acceptancementioning
confidence: 93%
“…Just world beliefs are frequently manipulated as an individual difference variable, which is hypothesized to have a causal effect on victim blaming (Lambert & Raichle, 2000). Support for this theory is found in many studies investigating rape victim blaming (Furnham, 2003;Whatley & Riggio, 1993;Yamawaki, 2009); yet, other studies have not found support for this theory (Hammond, Berry, & Rodriguez, 2011) or have even found support for the opposite (Lambert & Raichle, 2000). For example, Kleinke and Meyer (1990) found that women with high just world beliefs tend to view rape victims more favorably and blame them to a lesser extent than those with lower beliefs in a just world; a finding which is in direct contrast to that which would be expected if extrapolating directly from the theory.…”
Section: Just World Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…This separation from the state may lead Buddhism to have less direct influence on rape and rape myths. Admittedly, rape myths and high rates of rape are found in East Asian culture (e.g., Lee et al 2010;WHO 2005;Yamawaki 2009), but Buddhism seems to play a weaker role in creating and sustaining these myths than Christianity, Judaism, and the religions discussed here.…”
Section: Buddhismmentioning
confidence: 82%